Sistem Informasi Sekolah Digital SMP Negeri 5 Berbasis Website - Leni Marlina; Hermansyah (Jurnal Nasional Teknologi Komputer, 2025)
This study aims to design and implement a website-based digital school information system at SMP Negeri 5, which is expected to improve the efficiency of educational management and information access for students, teachers, and parents. The method used in this study is system development with an Agile approach, which includes the stages of needs analysis, design, implementation, and evaluation. The results of the study indicate that the developed information system is able to provide important features such as student data management, class schedules, announcements, and discussion forums. The system trial showed a positive response from users, with a user satisfaction level reaching 85%. In addition, this system also provides easy access to real-time information, thus supporting a more effective teaching and learning process. This study recommends further development for system integration with e-learning applications and training for users to maximize the benefits of the Digital School information system being promoted by the government. Thus, the website-based digital school information system at SMP Negeri 5 is expected to serve as a model for other schools in facing the challenges of education in the digital era and the rapid development of technology that requires schools to have a teaching model that is appropriate to the development of Gen Z.